2019
DOI: 10.37859/jp.v9i2.1265
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Kejadian Anemia Pada Remaja Putri Di SMA Negeri 1 Reteh Kecamatan Reteh Kabupaten Indragiri Hilir Tahun 2019

Abstract: Anemia is a condition where there is a decrease in the number of red cell mass which is indicated by adecrease in hemoglobin level <11 g / dl, hematocrit, and erythrocyte count (red cell count). The Indragiri HilirDistrict Health Office for girlsin 2016 amounted to 22.8% of 880, 201 young women who experienced anemia.General Objectives Describe and determine Determinants that affect the incidence of anemia in youngwomen in SMA 1 Reteh in 2018. This type of research is observational analytic with Cross Secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
0
0
1
Order By: Relevance
“…Based on the results of the Chi square test described in table 3, a p-value of 0.043 was obtained (p-value <0.05), so it was concluded that there was a significant relationship between the level of knowledge and the incidence of anemia in female adolescent in Dawungsari Village, Cilawu Health Center Working Area Garut in 2023. The results of this study support the results of Warlenda et al (2019); Kusnadi (2021);and Hasana et al (2023). The Odds Ratio (OR) value was 2.496, which means that female adolescent with a low level of knowledge have a 2.496 times higher chance of experiencing anemia compared to female adolescent with a high level of knowledge.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the results of the Chi square test described in table 3, a p-value of 0.043 was obtained (p-value <0.05), so it was concluded that there was a significant relationship between the level of knowledge and the incidence of anemia in female adolescent in Dawungsari Village, Cilawu Health Center Working Area Garut in 2023. The results of this study support the results of Warlenda et al (2019); Kusnadi (2021);and Hasana et al (2023). The Odds Ratio (OR) value was 2.496, which means that female adolescent with a low level of knowledge have a 2.496 times higher chance of experiencing anemia compared to female adolescent with a high level of knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…research ( 2021) with a literature study found that knowledge about anemia has a relationship with the incidence of anemia in female adolescent . The results of this study are also supported by the results of Warlenda et al (2019) ;Hasana et al (2023) . Research Nurhayati et al (2023) found that knowledge is a predisposing factor that influences adolescents' susceptibility to anemia.…”
Section: Introductionsupporting
confidence: 91%
“…Mereka menerapkan perilaku tersebut karena memperhitungkan risiko yang terjadi bila tidak menerapkan hidup sehat. Dalam hal ini, pengetahuan remaja tentang anemia berhubungan dengan kejadian anemia yang dialaminya (Sherly Vermita Warlenda et al, 2019). Pemberian informasi anemia sejak remaja sangat dibutuhkan agar terjadi peningkatan pengetahuan remaja salah satunya dampak anemia.…”
Section: Gambar 2 Media Promosi Melalui Instagramunclassified
“…Jumlah penduduk usia remaja putri (10-19 tahun) di Indonesia sebesar 26,2% yang terdiri dari 50,9% laki-laki dan 49,1% perempuan. (Vermita w et al, 2019). Berdasarkan data Riskesdas 2018, prevalensi anemia pada remaja sebesar 32%, artinya 3 -4 dari 10 remaja menderita anemia.…”
Section: Pendahuluanunclassified